Versatility in the medicinal use of mandacaru (Cereus jamacaru) Cactaceae / Versatilidade no uso medicinal de mandacaru (Cereus jamacaru) Cactaceae - Janilo Italo Melo Dantas; Maria Gisely Barbosa de Oliveira (Universidade Estadual de Alagoas, 2019)
Cereus jamacaru, popularly known as mandacaru, is a plant species native to the caatinga biome, which has important cultural, economic and environmental value. Like other types of plant species, mandacaru has been heavily used as a strategy to cure certain diseases in various local populations. Its strong use as a medicinal strategy has become highly versatile and can be seen in the descriptions of some ethnobotanical studies that have been carried out frequently in several local populations. In this context, this study aimed to describe the different medicinal indications of Mandacaru (Cereus jamacu) described in some Brazilian ethnobotanical works already performed. In order to do so, a scientific review was carried out using Scientific Electronic Library Online (SCIELO), through scientific articles that had already carried out ethnobotanical studies and identified the use of the species in some local populations of Brazil. A total of 14 scientific articles were analyzed, and it was possible to identify a total of 21 diseases combated or relieved by Cereus jamacaru, as well as; headache, kidney problems, diuretics, flu, syphilis, ulcer, gastritis, strokes, fractures, cancer, sinusitis, digestive disorders, diarrhea, snakebite, hemorrhoid, prostate, tuberculosis, spinal pain, stomach problems and heart problems. In this way, a wide use and versatility of the species is evidenced as a medicinal source by several local populations in different states of the Brazilian northeast region. The importance of this species is evident since it presents a popular, traditional and cultural pharmacological value for many people, and this knowledge must be preserved and valued with the species itself.